Benefits and limitations of humanized mouse models for human red blood cell-related disease research - Chen, Bing; Liu, Haochuan; Liu, Zhengang; Yang, Fan (Frontiers in Hematology, 2023)
Humanized mouse models with functional human genes, cells, and tissues are typically used for in vivo studies of diseases. Decades of studies on humanized mouse models have improved our understanding of hematopoiesis, infectious diseases, cancer biology, innate and adaptive immunity, and regenerative medicine. This review discusses the establishment and development of humanized mouse models and how they are used to model red blood cell-related diseases facilitating research in several biomedical disciplines. Furthermore, we provide approaches to overcome the limitations of these models.